Riding therapy on the perception of parents/mothers of autistic (Research, Society and Development, 2021)
This study aimed to understand the perception of fathers/mothers of individuals with Autistic Spectrum Disorder regarding participation in horse-assisted therapy. A qualitative exploratory-descriptive study with a cross-sectional design, conducted with sixteen parents of individuals with Autistic Spectrum Disorder participating in the Extension Project in Riding Therapy, linked to a Community University located in the north of the State of Rio Grande do Sul. Data were collected from November to December 2020, through individuais interviews using a semi-structured questionnaire. The parents' speeches were systematized by NVivo ®10, which generated categories of similarities and correlations, using Bardin's thematic content analysis. The fathers/mothers showed the perception of benefits related to coexistence and development, motor changes and social interaction, as well as the difficulties generated by the Covid-19 pandemic.